Regulation of Commercial Dispute Settlement Mediation in the Perspective of Legal Assurance and Justice - Umar Hasan; Suhermi Suhermi; Sasmiar Sasmiar (Universitas Sultan Ageng Tirtayasa, 2022)
The Indonesian government is currently trying to formulate an appropriate and up-to-date formula for making regulations on mediation and settlement of commercial disputes. This is done by the Indonesian government to support various policies that have been made to ensure legal certainty so that investment develops. Therefore, the authors are interested in bringing up the theme of this scientific article by analyzing comparative studies between Indonesia and Malaysia; The analysis in this article is about the mediation arrangement for the settlement of commercial disputes in Indonesia by comparing with Malaysia to achieve legal certainty and justice. The research method used is normative juridical. The results of the study show that the regulation of mediation for the settlement of commercial disputes in Indonesia as regulated in Law Number 30 of 1999 in substance and structure does not meet legal certainty and justice. Meanwhile in Malaysia, the arrangements for dispute resolution mediation regulated in the Kuala Lumpur Regional Arbitration Center Mediation Regulations and the 2012 Mediation Law (UU 749) have met legal certainty and justice. In the future, the concept of regulating commercial dispute settlement mediation in Indonesia, its substance and structure must meet legal certainty and justice. This scientific article concludes that the concept of regulating commercial dispute resolution mediation in Indonesia must be regulated separately because in substance and structure, mediation and arbitration have different principles. It is preferable that the regulations that will be made in the future must involve various parties related to the business world to produce representative regulations both nationally, regionally and internationally; if necessary, Indonesia becomes an alternative legal model for dispute resolution through mediation.